Prevalence of malnutrition, obesity and nutritional risk of Australian paediatric inpatients: A national one‐day snapshot. (15th August 2014) - White, Melinda; Dennis, Nicole; Ramsey, Rebecca; Barwick, Katie; Graham, Christie; Kane, Sarah; Kepreotes, Helen; Queit, Leah; Sweeney, Annabel; Winderlich, Jacinta; Wong See, Denise; Littlewood, Robyn
<x xml:space="preserve">Abstract</x> Aim Low prevalence rates of malnutrition at 2.5% to 4% have previously been reported in two tertiary paediatric Australian hospitals. The current study is the first to measure the prevalence of malnutrition, obesity and nutritional risk of paediatric inpatients in multiple hospitals throughout Australia. Methods Malnutrition, obesity and nutritional risk prevalence were investigated in 832 and 570 paediatric inpatients, respectively, in eight tertiary paediatric hospitals and eight regional hospitals across Australia on a single day. Malnutrition and obesity prevalence was determined using z‐scores and body mass index (BMI) percentiles. High nutritional risk was determined as a Paediatric Yorkhill Malnutrition Score of 2 or more. Results The prevalence rates of malnourished, wasted, stunted, overweight and obese paediatric patients were 15%, 13.8%, 11.9%, 8.8% and 9.9%, respectively. Patients who identified as Aboriginal and Torres Strait Islander were more likely to have lower height‐for‐age z‐scores (P < 0.01); however, BMI and weight‐for‐age z‐scores were not significantly different. Children who were younger, from regional hospitals or with a primary diagnosis of cardiac disease or cystic fibrosis had significantly lower anthropometric z‐scores (P = 0.05). Forty‐four per cent of patients were identified as at high nutritional risk and requiring further nutritional assessment. Conclusions The prevalence of malnutrition and nutritional risk of Australian paediatric inpatients on a given day was much higher when compared with the healthy population. In contrast, the proportion of overweight and obese patients was less.